PEMBELAJARAN BAHASA ARAB BERBASIS MEDIA SURAH MUTAHARRIKAH MULAWWANAH PADA KELAS CI+BI di MTs NEGERI SUMBER BUNGUR PAMEKASAN - Achmad Muchlis (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
Arab Ianguage does not only come from words released by utterance ( vokal) but also uses Ianguage, signal or picture Ianguage. Language Arab study is expected to assist educative participants recognize x'self, his cultural, and others culture, media surah mutaharrikah mulawwanah represents one of the alternative media in efficacy of Arab Ianguage study. Teacher will feel to be assisted in arranging its study process. Media availibility,specially surah mutaharrikah mulawwanah in a class will influence the student study where location of appropriate media will support attainment process of the arab language study itself . Through research by using approach qualitative, with exploration technique or analysis descriptive with cases manner, about Arab Ianguage study bases on media surah mutaharrikah mulawwanah at CI+BI class specially in MTS Negeri Sumber Bungur Pamekasan to strengthen finding about study theory of more quality. Research result obtained show; a) that CI+BI class MTS Negeri Sumber Bungur Pamekasan does the steps of unique study, among its unique is to defining mufrodat and qowaid before entering at istima', kalam, qiro’ah and kitabah items, b) motivation, student talent and enthusiasm in Arab Ianguage study in CI+BI class MTS Negeri Sumber Bungur Pamekasan can expand and show the improvement which enough significance if it is supported by teacher and study media matching with educative participant characteristic.